High pressure dewatering rolls: Comparison of a novel prototype to existing industrial technology. (21st September 2019) - Höfgen, Eric; Collini, Davide; Batterham, Robin J.; Scales, Peter J.; Stickland, Anthony D.
Graphical abstract: Highlights: A novel dewatering device, called High Pressure Dewatering Rolls has been developed. Industrial sludges were tested achieving similar results as state-of-the-art devices. Material characterisation for dewatering and shear strength properties are measured. Material properties can be used for modelling for comparison with other devices. Abstract: The optimisation of solid-liquid separation or dewatering processes for more efficient operation and reuse of material streams is of high importance. Suspension dewatering aims to increase the solids concentration and exhibits two limitations: the dewatering extent and the rate. A novel dewatering device, called High Pressure Dewatering Rolls (HPDR), has been developed. It combines shear and compression while maintaining a short filtration length between the rollers. The HPDR challenges the limitations of dewatering processes through the application of high pressures and induced shear to aid the extent of dewatering, and a short filtration length to allow fast dewatering. A prototype HPDR is described along with a performance assessment for different operating conditions as well as a comparison against state-of-the-art technology for a variety of industrial suspensions. The results demonstrate that the HPDR prototype, without any optimisation, outperforms or achieves comparable cake solids concentrations to existing equipment in a continuous mode of operation. Analysis of energy consumption and throughput remain outstanding and require further prototype development.